The Relevance of Al-Ghazali's Thought to Modern Education: A Literature Review on Ethics, Morals, and Character Development - Yahya, Muhammad; Putri, Selfi Regina; Putri, Ririn Mardana; Ariady, Silva (Khalaqa: Journal of Education and Learning, 2025)
This study aims to examine the relevance of Imam Al-Ghazali's thoughts to the modern education system, particularly in shaping the ethics, morals, and character of students. Amidst the current of globalization marked by technological advances and a moral crisis, Al-Ghazali's ideas have strategic value as a philosophical and spiritual basis for developing holistic education that focuses not only on intellectual aspects but also on moral and spiritual development. This study uses a qualitative approach. using the literature research method, through a study of Al-Ghazali's main works such asIhya’ Ulum al-Din, Ayyuha al-Walad, And The Scale of Action, as well as secondary literature in the form of books, scientific journals, and relevant research findings from the past decade. The study's findings indicate that Al-Ghazali viewed education as a process of purifying the soul (tazkiyat al-nafs) and developing noble morals through the integration of knowledge, faith, and good deeds. Teachers serve as both moral role models and guides. spiritual,while students are required to seek knowledge with intention sincerity and proper etiquette. Al-Ghazali's concept of ideal education is one that balances intellectual, moral, and spiritual dimensions. This finding confirms that Al-Ghazali's ethical educational thinking remains relevant in the context of modern education, as it can provide a solution to the moral crisis and encourage the formation of a generation that is knowledgeable, devout, and has noble morals and plays an active role in community life